2017
DOI: 10.1155/2017/5141032
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Osteomyelitis of the Distal Femur Treated with Resection and Delayed Endoprosthetic Reconstruction: A Report of Three Cases

Abstract: Chronic osteomyelitis involving the distal femur often results in amputation or arthrodesis. This article presents three cases of chronic osteomyelitis treated with a staged approach culminating in endoprosthetic reconstruction. Stage one involved resection of infected bone and placement of an intramedullary nail spanning the bony defect between proximal femur and tibia, with antibiotic cement packed around the nail. Patients were then placed on long-term IV +/− oral antibiotics to clear the infection. A “cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This also shows that the cure of chronic osteomyelitis needs a long process of diagnosis and treatment, can not rush for a while. Kanakaris, et al [11,12] suggested that patients with chronic osteomyelitis should be treated in stages, because there is a risk of reinfection caused by residual pathogenic bacteria in soft tissue after debridement, early internal fixation is not allowed in patients with osteomyelitis. In our case, thorough debridement, catheter irrigation and external fixator will be carried out in the early stage of treatment, the next stage of treatment will be carried out when there is evidence that the infection is completely controlled.…”
Section: Discussionmentioning
confidence: 99%
“…This also shows that the cure of chronic osteomyelitis needs a long process of diagnosis and treatment, can not rush for a while. Kanakaris, et al [11,12] suggested that patients with chronic osteomyelitis should be treated in stages, because there is a risk of reinfection caused by residual pathogenic bacteria in soft tissue after debridement, early internal fixation is not allowed in patients with osteomyelitis. In our case, thorough debridement, catheter irrigation and external fixator will be carried out in the early stage of treatment, the next stage of treatment will be carried out when there is evidence that the infection is completely controlled.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, suggest amputation to be performed, but his family refused it [ 3 ], [ 5 ], [ 8 ], [ 19 ], [ 20 ]. Consequently, we performed radical debridement and excision of all avascular scarred and infected granulation tissue, followed by debridement of the infected endosteum, reaming, and the insertion of closed suction drainage system [ 3 ], [ 20 ], [ 21 ].…”
Section: Discussionmentioning
confidence: 99%